Current and potential contributions of large-scale food fortification to meeting micronutrient requirements in Senegal: a modelling study using household food consumption data - Katherine P Adams; Reina Engle-Stone; Brent Wibberley; Becky L Tsang; Ann Tarini; Maguette Beye; Laura A Rowe (BMJ Publishing Group, 2024)
Introduction Micronutrient deficiencies are common among women of reproductive age (WRA) and children in Senegal. Large-scale food fortification (LSFF) can help fill gaps in dietary intake.Methods We used household food consumption data to model the contributions of existing LSFF programmes (vitamin A-fortified refined oil and iron and folic acid-fortified wheat flour) and the potential contributions of expanding these programmes to meeting the micronutrient requirements of WRA (15-49 7 years) and children (6-59 months).Results Without fortification, apparent inadequacy of household diets for meeting micronutrient requirements exceeded 70% for vitamin A, thiamin, riboflavin, folate and zinc, was 61% for iron among WRA (43% among children) and was ~25% for vitamin B12. At estimated current compliance, fortified refined oil was predicted to reduce vitamin A inadequacy to ~35% and could further reduce inadequacy to ~25% if compliance with the standard improved. Fortified wheat flour at estimated current compliance reduced iron and, especially, folate inadequacy, but improvements in compliance would be necessary to achieve the full potential. Beyond existing programmes, expanding wheat flour fortification to include additional micronutrients was predicted to have a modest impact on thiamin and riboflavin inadequacies and larger impacts on vitamin B12 and, especially, zinc inadequacies. Adding a programme to import fortified rice could further reduce inadequacies of multiple micronutrients (generally by >10 percentage points), although potential risk of high intake of vitamin A, folic acid and zinc among children should be carefully considered. With both wheat flour and rice fortification, predicted prevalence of vitamin A, iron and zinc inadequacy remained above 25% in some regions, pointing to the potential need for coordinated, targeted micronutrient interventions to fully close gaps.Conclusions When considered alongside evidence on the cost and affordability of these programmes, this evidence can help inform the development of a comprehensive micronutrient intervention strategy in Senegal.